Identification of Infectious Bacteria in Dental Units - Maryam Moradnia; Shaghayegh Mousavi; Mohammad Darvishmotevalli; Hossein Karimi; Fatemeh Fotoohi Qazvini (International Journal of Environmental Health Engineering)
Aim: The aim of this study was to determine the bacterial contamination of surfaces and water of dental units of Qazvin University of Medical Sciences. Methods: This cross-sectional descriptive study was conducted on the surgery and periodontal units at the Faculty of Dentistry, Qazvin University of Medical Sciences in 2017. Totally, 108 samples were collected from different parts of the dental units. Total Staphylococcus aureus, Pseudomonas aeruginosa, Legionella pneumophila, and Escherichia coli were counted before and after disinfection by deconex. Results: The results of this study showed that before and after disinfection, S. aureus, P. aeruginosa, and Coliforms were the most frequent bacteria in periodontal (100%, 100%, and 100%, respectively) and surgery wards (100%, 100%, and >83%, respectively). There was no significant relationship between pre and postdisinfection in terms of S. aureus and P. aeruginosa for other parts of the surgery and periodontics units (p >0.05). Furthermore, the statistical results indicated that all parts of the surgery and periodontics surfaces were statically significant pre and postdisinfection in term of Coliforms (p < 0.05). Conclusion: It can be concluded that the rate of microbial pollution in water lines and surfaces of the dental units is high. Furthermore, since a significant number of bacteria were identified after disinfection, it indicates the improper use of disinfectants.